Public preferences for electricity contracts including renewable energy: A marketing analysis with choice experiments. (August 2015) - Vecchiato, Daniel; Tempesta, Tiziano
Abstract: This study aims to understand people's preferences concerning different energy sources with a particular focus on renewables. Households' preferences were assessed by means of a choice experiment on a sample of people living in Veneto (north eastern Italy). The analysis considered real marketing scenarios, presenting different choice options inspired by real market offers by different companies on the Italian market. The energy packages were differentiated considering the monthly price, the source of the energy package (solar, biomass from agriculture and biomass from forestry), the size of the power plants, the minimum distance from houses, and, for biomass only, the certification of the origin. According to our results, there is a wide market for expanding "green" electricity contracts: 86% of the respondents stated that they are willing to pay more for them. People prefer electricity produced from photovoltaics, followed by forest biomass and by agricultural biomass. According to our results, the possibility to choose the renewable energy source matters: the willingness to pay for photovoltaic is 3.4 times that for forest biomass and 5.4 times that for agricultural biomass. Highlights: We analysed the preferences for energy contracts from renewables. Our sample is willing to pay more for "green" energy contracts. Differences were found in the willingness to pay for different energy sources. Solar photovoltaic is preferred to biomass. Forest biomass is preferred to agricultural biomass.